Antimacrobial Properties of gynura procumbens (Sambung Nyawa) leaves In methanolic and acidic extracts - Haron, Normah; Mat Jusoh, Hanapi (KULLIYYAH OF ALLIED HEALTH SCIENCES, IIUM, 2019)
Introduction: Gynura procumbens, commonly known as ‘sambung nyawa’ in Malaysia has been used traditionally as remedies for anti-inflammatory, anti-hyperlipidimic and anti-hyperglycemic. The purpose of the present study was to qualitatively evaluate the antimicrobial effects of Gynura procumbens extracts. Methods: The sample was extracted using methanol and acid hydrolysis. The antimicrobial effects of the sample were determined by disc diffusion method against two bacteria and two fungi namely E. coli, S. aureus, C. albicans and S. cerevisiae. Results: The results showed that the acidic extract of G. procumbens has positive reactions towards E. coli, S. aureus and C. albicans with the presence of zone of inhibition at the concentration of 150 mg/mL. Following the positive reaction, the minimum inhibitory concentration (MIC) of the acidic extract was then evaluated by broth dilution method. The MIC of E. coli and S. aureus were determined at concentration 37.5 mg/mL and 75 mg/mL for C. albicans. It indicated that acidic extracts at lower concentration could inhibit the bacteria, but high concentration of extracts was required in the inhibition of the fungi. Conclusion: It can be concluded that, the present study proves that there is potential of antimicrobial effects in Gynura procumbens leaves extracts.